2015
DOI: 10.1590/s1806-92902015001200001
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming dormancy and determining optimal temperature for slender serradella seed germination

Abstract: -The objective of this study was to identify the most efficient method for overcoming coat-imposed dormancy and determine the optimal germination temperature for Ornithopus pinnatus seeds. Treatments to overcome dormancy were: intact seeds; immersion in hot water at 60 ºC, followed by soaking in the same water (unheated)/24 h; immersion in hot water at 90 ºC, followed by soaking in the same water (unheated)/24 h; mechanical scarification; chemical scarification, H 2 SO 4 /5 min; and chemical scarification, H 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
(24 reference statements)
1
3
0
1
Order By: Relevance
“…As per the findings Yazdanpanah et al (2012) of a high percentage of germination is achieved through scarification of seeds with sandpaper (65%). The same observations were also made by Sanjana and Jeya (2013); Lopes et al (2015), who reported that the seeds that were mechanically scarified exhibited very high germination percentage compared with any other seed treatment.…”
Section: Germination Percentsupporting
confidence: 81%
“…As per the findings Yazdanpanah et al (2012) of a high percentage of germination is achieved through scarification of seeds with sandpaper (65%). The same observations were also made by Sanjana and Jeya (2013); Lopes et al (2015), who reported that the seeds that were mechanically scarified exhibited very high germination percentage compared with any other seed treatment.…”
Section: Germination Percentsupporting
confidence: 81%
“…This temperature variation is called thermos-inhibition, which is characterized by the absence of germination when the temperature is slightly above the optimum conditions [36]. Germination inhibition by high temperatures (25 • C-30 • C) has been observed in other species, such as Spinacia oleracea L. [17,18], Ornithopus pinnatus [19], and Myrsine parvifolia [20], and the seeds of these three species have also shown higher final germination at temperatures of 15 • C and 20 • C, while significantly lower germination occurred at 25 • C and 30 • C.…”
Section: Responses Of Germination To Temperaturementioning
confidence: 99%
“…For example, either no germination or extremely low germination was observed at 25 • C and 30 • C, while high final germination was obtained when seeds were incubated at lower temperatures of 15 • C and 20 • C for species such as Pinacia oleracea L. [17,18], Ornithopus pinnatus (Mill.) Druce [19], and Myrsine parvifolia A. DC. [20], and coniferous species of Pinus halepensis Miller and Pinus brutia Tenore [21].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Javaid et al (2010) reported of prolonged seed dormancy in P. hysterophorus with increasing temperature. Lopez et al (2015) reported that the germination process of plant species is generally synchronized within the optimum temperature range. These results indicate that IAPs such P. hysterophorus could enhance its persistence in the environment and opportunity for developing into new invasions by temporal variations in seed germination due to non-synchronized breaking of seed dormancy.…”
Section: Weeds Invasive Alien Plants and Climate Impacts -Implicationsmentioning
confidence: 99%